Relevansi Antara Kondisi Penyelenggaraan dengan Buku Petunjuk Teknis Penyelengaraan Taman Penitipan Anak (TPA) di Kecamatan Bumiayu - Eko Sulistyasih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: The purpose of this study, firrst, to know the operation of the Daycare institution in Bumiayu District. Second, to determine the relevance of the conditions of implementation technical manual operation of Daycare in Bumiayu District. This research using quantitative is of the descriptive approach. The population in this study were 3 managers in the third Daycare above, 6 educators at Lestari Daycare, 4 educators at al-Ikhlas Daycare, and 1 educators at Bina Mandiri Daycare. The small of population makes the researcher does not take the some of them as samples. The results that: there is a match between the showed condition of implementation of the technical manual operation of Lestari Daycare. Meanwhile, the condition of the implementation of the technical manual operation of al-Ikhlas and Bina Mandiri Daycare are quite appropriate. Keywords: Daycare, relevance, user guide.